Multinational ownership patterns and anti-tax avoidance legislation - Axel Prettl; Dominik von Hagen (International Tax and Public Finance, 2022)
We investigate whether controlled foreign corporation (CFC) rules influence cross-border merger and acquisition (M&A) activity on a global scale. CFC rules are one main anti-tax avoidance measure and potentially lead to immediate taxation of foreign subsidiaries' income at parent level. Analyzing a large M&A data~set and detailed self-compiled CFC rule data from 27 countries using two different econometric perspectives, we show if and how CFC rules distort firm behavior and ownership patterns. First, we find that the probability of being the acquirer of a low-tax target decreases if CFC rules may be applicable to this target's income. Second, we show that CFC rules alter an acquirer's choice of targets' location. Altogether, our study shows that for affected acquirer countries, CFC rules lead to less M&A activity in low-tax countries due to potentially reduced incentives to shift income. However, these effects appear to be rather small in size and decrease over time. Thus, our study suggests that CFC rules do not substantially bias the market for corporate control as lobby groups partially claim and policy makers can be confident in reaching their goals of diminishing profit shifting with this increasingly important anti-tax avoidance rule.
Keywords: F23; G34; H25; H26; H32; H73; 340; CFC rules; M&A; International taxation; Tax avoidance